Developing Google Sites-Based E-Modules to Enhance Teachers’ ICT Competence at Al Husna Foundation - Ilma Fauziana Fariz; Sholeh Hidayat; Isti Rusdiyani (AL-ISHLAH: Jurnal Pendidikan, 2025)
Integrating Information and Communication Technology (ICT) into teaching remains a significant challenge for many educators, particularly those at Yayasan Al Husna, Tangerang, who continue to rely on traditional methods despite available digital tools. Enhancing teachers’ ICT competence is essential to support more effective and engaging learning experiences. This study aimed to develop a Google Sites-based e-module to improve teachers' abilities in creating interactive, web-based instructional materials. The research employed the ADDIE instructional design model (Analysis, Design, Development, Implementation, and Evaluation) and adopted a mixed-methods approach. Data were collected through structured interviews, expert validations, questionnaires, and pre-post tests. Expert validation results showed a feasibility rating of 70% from a content expert and 92% from a media expert, classifying the e-module as "very valid." The module includes structured content with step-by-step tutorials, visual aids, and interactive exercises. During implementation with 17 teachers, the e-module demonstrated high usability and practicality. Pre- and post-test comparisons showed a moderate improvement in ICT competence, with an average N-Gain score of 0.66. The findings suggest that the developed e-module is effective in enhancing teachers' ICT skills, particularly in designing digital learning materials using accessible platforms. This study provides a replicable model for teacher professional development in schools with limited digital adoption. Future research could explore broader implementation across diverse educational settings.